1997
DOI: 10.1111/j.1751-0813.1997.tb15709.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of cutaneous infections of Myxobolus episquamalis (Myxozoa: Myxobolidae) in sea mullet, Mugil cephalus L, in Australia

Abstract: The infection is widespread in Australian mullet, but rarely causes significant economic loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 11 publications
1
14
0
1
Order By: Relevance
“…The infection site and morphological characteristics of the spores observed from the scales in this study are similar to those reported (Egusa et al 1990;Rothwell et al 1997;Diamanka et al 2008;Kim et al 2013). In addition, 18S rRNA sequence data of the spores showed 100% homology to M. episquamalis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The infection site and morphological characteristics of the spores observed from the scales in this study are similar to those reported (Egusa et al 1990;Rothwell et al 1997;Diamanka et al 2008;Kim et al 2013). In addition, 18S rRNA sequence data of the spores showed 100% homology to M. episquamalis.…”
Section: Discussionsupporting
confidence: 90%
“…Myxobolus episquamalis infects the epithelial tissues of the scales and fins (Rothwell et al 1997). Previous reports of this parasite describe up to 70% of the body of M. cephalus covered in lesions (Diamanka et al 2008).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…According to previously described species, 15 species belonging to the Myxobolus genus have been demonstrated to infect mullet (Bahri and Marques 1996). Myxobolus species infecting mullet have been reported on various geological regions including the west coast of Tunisia, Mediterranean coast, in the Atlantic at Ria de Aveiro in northern Portugal, South Florida coast, Australia, and the Japanese coast Rothwell et al 1997;Diamanka et al 2008;Umur et al 2010). All characteristics of this new species were also compared to confirm morphological similarities to the spores of different species of the genus Myxobolus described previously (see Table 1).…”
Section: Morphological and Ultrastructural Taxonomic Classificationmentioning
confidence: 95%
“…This indicates that infection, development, and spore maturation occurs within the first few months of life. A number of myxozoan parasites have been shown to infect primarily young fishes, especially in spring and early summer (Kent et al 1994, Rothwell et al 1997, Holzer & Schachner 2001. Other examples of myxosporean infections of young fishes include proliferative kidney disease in trout, whereby the fish are infected during April and May (Foote & Hedrick 1987), Sphaerospora truttae in salmon (Ozer & Wootten 2000), Myxobolus cerebralis infection in the rainbow trout Oncorhynchus mykiss (Markiw 1991), Myxobolus episquamalis infection in the sea mullet Mugil cephalus in the spring (Rothwell et al 1997), and Kudoa thyrsites infection in Atlantic salmon (St-Hilaire et al 1998).…”
Section: Kudoa Clupeidae Development In Atlantic Menhadenmentioning
confidence: 99%